ChemInform Abstract: Isoselenazolones as Catalysts for the Activation of Bromine: Bromolactonization of Alkenoic Acids and Oxidation of Alcohols. Issue 9 (5th March 2013) - Balkrishna, Shah Jaimin; Prasad, Ch. Durga; Panini, Piyush; Detty, Michael R.; Chopra, Deepak; Kumar, Sangit
Abstract The isoselenazolone (ISA) efficiently promotes bromolactonization of alkenoic acids, oxidation of secondary alcohols, as well as bromoesterification of alkenes and alkynes.Both processes proceed with good to high regio‐ and stereoselectivity.